Ионная смола в магнитном поле; Полифункциональные химические материалы и технологии - Мышкин В. Ф. Вячеслав Фёдорович; Хан В. А. Валерий Алексеевич; Тундешев Н. В.; Цхе А. В. Алексей Викторович (2013, 2013)
В фонде НТБ ТПУ отсутствует